Training of Resin Keychain Making Based on Local Wisdom for Supporting Independent Entrepreneurship Program of Independent Campus - Rahmawati, Helda; Muna, Khairiatul; Marisa , Lutfiana; Rasid, Saipul; Hasriati; Ummi , Sayyidatul; Bahit , Muhammad (Journal of Saintech Transfer, 2024)
The community service activity was carried out based on the results of a needs survey for community service implementation, which has been distributed to active students from various academic and vocational programs of Chemistry Education program in South Kalimantan. The need analysis survey results showed that students are already aware of the independent curriculum, but many of them are still unaware of the independent entrepreneurship program. In addition, students also hope for entrepreneurship training, such as keychain making training. The method used in the community service is the introduction to resin materials and training in making resin keychains. The training activities were conducted in the integrated laboratory of Universitas Islam Negeri Antasari with a total of 60 participants. The results obtained from this community service are that students acquire new skills in making resin keychains, which can be used as products for entrepreneurship. The pretest showed that initially the participants' insight did not know and recognize resin and catalyst materials, and the result of the posttest showed that the participants were able to be creative by using dried flowers, leaves, and grass typical of the surrounding area to produce beautiful resin key chains.